2017
DOI: 10.1111/ddi.12685
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution patterns can predict the local habitat specialization of arachnids in heterogeneous landscapes of the Atlantic Forest

Abstract: Aim This study formally evaluates the ability of three models to use geographical data on species distribution to predict the habitat use patterns of species in heterogeneous landscapes. Location Species and habitats in the Brazilian Atlantic Rain Forest were investigated. Methods Based on empirical data on harvestmen and scorpions, we estimated the strength of species association with preferred habitat and classified them as habitat generalists or habitat specialists. We compared these empirical results with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
(129 reference statements)
0
3
0
2
Order By: Relevance
“…Porto et al (2018) observed that most har-vestmen taxa had a limited geographic range and were closely tied to specific habitats. Out of the abundant species they sampled, three quarters were forest specialists, and the remainder specialized in open areas (Porto et al 2018). Thus, habitat type and microhabitat can have major proximal effects on harvestmen abundance and species composition.…”
Section: ] Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porto et al (2018) observed that most har-vestmen taxa had a limited geographic range and were closely tied to specific habitats. Out of the abundant species they sampled, three quarters were forest specialists, and the remainder specialized in open areas (Porto et al 2018). Thus, habitat type and microhabitat can have major proximal effects on harvestmen abundance and species composition.…”
Section: ] Discussionmentioning
confidence: 99%
“…However, they observed substantial differences between harvestmen taxa inhabiting the ground/litter layer and those inhabiting the shrub/tree layer, indicating specific habitat and microhabitat preferences within a forest stand (Proud et al 2012). Porto et al (2018) observed that most harvestmen taxa had a limited geographic range and were closely tied to specific habitats. Out of the abundant species they sampled, three quarters were forest specialists, and the remainder specialized in open areas (Porto et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Homepage:https://periodicos.ufpe.br/revistas/rbgfe Paschoal., E., M.., A., D., Otoni., T., J., O., Gripp., A., M., Freire., J., P., Alves., P., L., Gonzaga., A., P., D., Machado., E., L., M. principais ameaças a biodiversidade (Xie et al, 2017;Santos et al, 2020). Os fragmentos remanescentes, por possuírem áreas de habitat menores, acabam suportando populações também menores, e onde os riscos de extinção são mais comuns (Porto et al, 2018). Isto porque o isolamento das populações leva à depreciação do fluxo gênico, aumento da endogamia e perda da heterozigose, favorecendo a ocorrência da extinção local ou até mesmo regional (Porto et al, 2018;Cruz et al, 2018).…”
Section: Issn:1984-2295unclassified
“…Os fragmentos remanescentes, por possuírem áreas de habitat menores, acabam suportando populações também menores, e onde os riscos de extinção são mais comuns (Porto et al, 2018). Isto porque o isolamento das populações leva à depreciação do fluxo gênico, aumento da endogamia e perda da heterozigose, favorecendo a ocorrência da extinção local ou até mesmo regional (Porto et al, 2018;Cruz et al, 2018). Tais consequências são ainda mais preocupantes quando ocorrem em ambientes que apresentam fragilidade ambiental, ou seja, quando os recursos naturais têm sido explorados durante séculos, incluindo, por exemplo, a ocupação antrópica na região da Mata Atlântica, o que proporcionou modificações na paisagem em larga escala e fragmentação florestal (Santos et al, 2020;Laurance, 2009;Ribeiro et al, 2009).Os altos níveis de fragmentação ainda observados atualmente, assim como, a contínua perda de habitat em toda a Mata Atlântica, têm gerado várias preocupações na comunidade científica (Joly et al, 2014;Esser et al, 2019).…”
Section: Issn:1984-2295unclassified
“…Large-scale analysis of habitat association de-emphasises the less frequent recordings of a species in a habitat in which the species is transient, which could be misconstrued at a small-scale as association. Although SDMs (Petit et al 2003, Phillips et al 2006, Porto et al 2018) and indicator species analyses (Hill et al 1975, Gardner 1991, Ricotta et al 2015 are often done over large scales, this is rare for analysis of the preference of a species. Exceptions are Eyre and Luff (2004), who used ordination to study habitat preferences of carabids in north east England and the Scottish Border, and Redhead et al (2016) who used general linear mixed effects models to study butterfly habitats across Britain.…”
Section: Introductionmentioning
confidence: 99%